1996
DOI: 10.1093/mnras/281.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a relativistic rotating electron-positron jet: non-axisymmetric perturbations

Abstract: We investigate the linear stability of a hydrodynamic relativistic flow of magnetized plasma in the simplest case where the energy density of the electromagnetic fields is much greater than the energy density of the matter (including the rest mass energy). This is the force-free approximation. We considered the case of light cylindrical jet in cold and dense environment, so the jet boundary remains at rest. Continuous and discrete spectra of frequencies are investigated analytically. An infinite sequence of ei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 24 publications
2
82
0
Order By: Relevance
“…See, for instance, the left panel in Fig 3. For larger magnetic field strengths (case B5), we observe a stable behavior even in long term integration, as shown in the right panel of Fig 3. In the regime of strong magnetizations, in fact, the system can be well described by the force-free approximation. In this limit, our simulation results are in agreement with the findings of Istomin & Pariev (1994), (1996 who have shown that a jet with a longitudinal electric current remains stable with respect to helical as well as axially symmetric (pinch) modes. We believe that the induced stability owes to the stabilizing action of the electric field and, therefore, it has to be considered as a purely relativistic effect.…”
Section: Periodic Jet Simulationssupporting
confidence: 91%
See 1 more Smart Citation
“…See, for instance, the left panel in Fig 3. For larger magnetic field strengths (case B5), we observe a stable behavior even in long term integration, as shown in the right panel of Fig 3. In the regime of strong magnetizations, in fact, the system can be well described by the force-free approximation. In this limit, our simulation results are in agreement with the findings of Istomin & Pariev (1994), (1996 who have shown that a jet with a longitudinal electric current remains stable with respect to helical as well as axially symmetric (pinch) modes. We believe that the induced stability owes to the stabilizing action of the electric field and, therefore, it has to be considered as a purely relativistic effect.…”
Section: Periodic Jet Simulationssupporting
confidence: 91%
“…Current driven instabilities have been studied in the non-relativistic linear limit by Appl & Camenzind (1993), while Relativistic Jets 411 relativistic linear studies have been presented by Istomin & Pariev (1994), (1996. Linear studies are strongly affected by the assumed boundary conditions and cannot follow the complex nonlinear effects that may damp unstable modes.…”
Section: Introductionmentioning
confidence: 99%
“…Cylindrical force-free jets are kink stable if the poloidal field is independent of the radius [65,66], but are kink unstable if the poloidal field decreases with the radius [50,53]. In a static reference frame or jet confined by rigid walls [67], the Kruskal-Shafranov criterion for instability, |B φ /B p | > 2πR/z, indicates that the instability develops if the length of a static plasma column is long enough for the field lines to go around the column at least once [68].…”
Section: Current Driven Instabilitymentioning
confidence: 99%
“…This instability excites large scale helical motions that may disrupt the system. Cylindrical force-free jets are kink stable if the poloidal field is independent of the radius (Istomin & Pariev 1994, Istomin & Pariev 1996, but cylindrical force-free jets are kink unstable if the poloidal field decreases with the radius (Begelman 1998;Lyubarskii 1999). In the case of non-relativistic rotation, force-free jets are kink unstable if |B φ /B p | > |Ω|R/c (Tomimatsu et al 2001).…”
Section: Current Driven Instabilitymentioning
confidence: 99%